Analisis Pengaruh Promosi Terhadap Keputusan Wisatawan Untuk Mengikuti Program Pakettourdi CV.Funtastic Tour And Travel - Furi Emadianti; Khoirul Umam; Ai Annisa Utami (RELASI : JURNAL EKONOMI, 2020)
The purpose of this study is to prove and determine how much influence the promotion of tourists' decision to join the tour package program at CV. Funtastic Tour and Travel with destinations in Bali, Lombok, and Malang, what factors influence the decision of tourists to join the Survey method program with a quantitative approach. Sampling using a purposive sampling method with data collection using a questionnaire through survey techniques. The total population studied was 100 people with a sample of 80 people from tourists who took the tour package program at CV. Funtastic Tour and Travel. The hypothesis is proven by the test Ttest= 6,192 compared to Ttable= 1,664 which means there is a significant influence between promotion and the decision of tourists to participate in the tour package program. The sensitivity level of consumer (traveler) decisions to the promotion itself is 83.8% indicated by the regression coefficient ????̂=6,087+0,838????. While the correlation coefficient shows r = 0.515 and the coefficient of determination (KD) of 27%. This means that promotion does not objectively influence tourists to participate in tour packages even though it is significantly able to influence tourists' decisions to participate in the tour program. Keywords:promotion, tourism, tourist decision, tour package program